2011
DOI: 10.1021/jf203760k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Analysis of Fatty Acids, Sterols, and Tocopherols in Eight Vegetable Oils

Abstract: The similarities and differences of eight vegetable oils produced in China were investigated in terms of their fatty acid, sterol, and tocopherol compositions and subsequent data processing by hierarchical clustering analysis and principal component analysis. The lipid profiles, acquired by analytical techniques tailored to each lipid class, revealed great similarities among the fatty acid profiles of corn and sesame oil as well as few differences in their sterol profiles. It turns out that not only was there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 28 publications
9
62
3
Order By: Relevance
“…Fatty acids exhibit rich variety, exhibiting variable fatty acid composition and content across species (and even across varieties). Therefore, fatty acid composition and content profiles can be used as fingerprints to identify useful biological resources, in addition to their current use for oil authentication (Li et al, 2011). At the species level, a total of 15 distinct fatty acid components were detected in this study (Table 2), the results are similar to Hu et al (2017), and a number similar to that was obtained for X. sorbifolia by Yu et al (2017), although their oil content differed from values reported here.…”
Section: Fatty Acid Compositionsupporting
confidence: 73%
“…Fatty acids exhibit rich variety, exhibiting variable fatty acid composition and content across species (and even across varieties). Therefore, fatty acid composition and content profiles can be used as fingerprints to identify useful biological resources, in addition to their current use for oil authentication (Li et al, 2011). At the species level, a total of 15 distinct fatty acid components were detected in this study (Table 2), the results are similar to Hu et al (2017), and a number similar to that was obtained for X. sorbifolia by Yu et al (2017), although their oil content differed from values reported here.…”
Section: Fatty Acid Compositionsupporting
confidence: 73%
“…Before being analyzed, the oils were pretreated as the following (Li, Yao & Zhao, 2011): First, 1.5 g of oils, together with 2 mL of 1 mg/mL 5α-cholestan-3β-ol (internal standard) in n-hexane, were saponified with 100 mL of 1 M methanolic potassium hydroxide at 85 °C for 1 h in a reflux condenser. After cooling, 25 mL of saturated sodium chloride was added, and the unsaponifiable matter was extracted with 3 × 50 mL of n-hexane.…”
Section: Sterols and Other Terpenic Compoundsmentioning
confidence: 99%
“…Tocopherols (Vitamin E) have received significant attention for their role as natural antioxidants, free radical quenchers and the extensive health benefits they provide in the cardiovascular, immune and metabolic processes in the human body (Granado-Lorencio et al, 2007;Kamal-Eldin and Appelqvist, 1996). Crude canola oil contains high concentrations of a-and g-tocopherol (a-T and g-T), approximately 270 and 420 mg/kg, respectively, which is comparable to those found in palm and sunflower oils, but considerably higher than olive oils (Kamal-Eldin and Andersson, 1997;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%